1996
DOI: 10.1177/026988119601000208
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sub-anaesthetic doses of ketamine on memory, cognitive performance and subjective experience in healthy volunteers

Abstract: The cognitive and subjective effects of sub-anaesthetic doses of ketamine on healthy volunteers were examined. Twelve healthy volunteers received 25 mg ketamine, 10 mg ketamine and saline placebo, i.m. in a double-blind, Latin square design. A cognitive, perceptual and self-report test battery was administered over 45 min. The order of tests was rotated to control for timing effects. Ketamine (25 mg) significantly affected verbal learning and memory, parallel visual search, some measures of psychomotor perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 22 publications
4
27
0
Order By: Relevance
“…Ketamine also reduced psychomotor speed on trailmaking in the present study, but did not affect trailmaking scores once psychomotor slowing had been controlled for. This replicates the findings of Harborne et al (1996), and indicates a preservation of some aspects of frontal functioning.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Ketamine also reduced psychomotor speed on trailmaking in the present study, but did not affect trailmaking scores once psychomotor slowing had been controlled for. This replicates the findings of Harborne et al (1996), and indicates a preservation of some aspects of frontal functioning.…”
Section: Discussionsupporting
confidence: 88%
“…It has been proposed that NMDA-receptor-mediated LTP is involved in both working and long-term memory in humans (Lisman et al, 1998). Indeed ketamine, when administered to healthy volunteers, induces deficits in performance on verbal and visual memory tasks (Adler et al, 1998;Harborne et al, 1996;Harris et al, 1975;Hetem et al, 2000;Krystal et al, 1994Krystal et al, , 1999Krystal et al, , 2000Malhotra et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported changes in measures of cognition, eye-tracking, and event-related brain potentials with ketamine in normal (Harborne et al 1996;Radant et al 1998;vanBerckel et al 1998;Oranje et al 2000;Weiler et al 2000) and SVs (LaPorte et al 1996;Malhotra et al 1997a). These results suggest that ketamine, when further studied, may induce additional symptoms of schizophrenia, particularly the cognitive.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is hard to see how generalized overactivity can be used to predict the specific changes in context-sensitivity and perceptual grouping emphasized throughout this article. Increases in activity, for Harborne et al (1996). example, as reflected by neuroimaging, are often assumed to be functional, not malfunctional.…”
Section: Nmda-antagonists Impair Cognitive Coordination and Are Schizmentioning
confidence: 99%